Biodistribution and safety of a live attenuated tetravalent dengue vaccine in the cynomolgus monkey. Issue 43 (13th October 2017) - Ravel, Guillaume; Mantel, Nathalie; Silvano, Jeremy; Rogue, Alexandra; Guy, Bruno; Jackson, Nicholas; Burdin, Nicolas
Highlights: Subcutaneous live, attenuated, tetravalent dengue virus vaccine (CYD-TDV) was well tolerated. No toxicological findings other than minor local reactions at the injection site. Transient low level of CYD-TDV RNA detected primarily in blood, the injection site and draining lymph nodes. Absence of toxicological concern with CYD-TDV. Abstract: Background: The first licensed dengue vaccine is a recombinant, live, attenuated, tetravalent dengue virus vaccine (CYD-TDV; Sanofi Pasteur). This study assessed the biodistribution, shedding, and toxicity of CYD-TDV in a non-human primate model as part of the nonclinical safety assessment program for the vaccine. Methods: Cynomolgus monkeys were given one subcutaneous injection of either one human dose (5 log10 CCID50 /serotype) of CYD-TDV or saline control. Study endpoints included clinical observations, body temperature, body weight, food consumption, clinical pathology, immunogenicity, and post-mortem examinations including histopathology. Viral load, distribution, persistence, and shedding in tissues and body fluids were evaluated by quantitative reverse transcriptase polymerase chain reaction. Results: The subcutaneous administration of CYD-TDV was well tolerated. There were no toxicological findings other than expected minor local reactions at the injection site. A transient low level of CYD-TDV viral RNA was detected in blood and the viral genome was identified primarily at the injection site and in the draining lymph nodes following immunization. Conclusions: These results, together with other data from repeat-dose toxicity and neurovirulence studies, confirm the absence of toxicological concern with CYD-TDV and corroborate clinical study observations.